Children’s Block-Building Skills and Mother-Child Block-Building Interactions Across Four U.S. Ethnic Groups - Suh, Daniel D.; Liang, Eva; Ng, Florrie Fei-Yin; Tamis-LeMonda, Catherine S. (Frontiers in Psychology, 2019)
Play offers an unparalleled opportunity for young children to gain cognitive skills in informal settings. Block play in particular—including interactions with parents around block constructions—teaches children about intrinsic spatial features of objects (size, shape) and extrinsic spatial relations. In turn, early spatial cognition paves the way for later competencies in math and science. We assessed 4- and 5-year-old children’s spatial skill on a set of block-building constructions and examined mother-child block building interactions in 167 U.S. dyads from African American, Dominican, Mexican, and Chinese backgrounds. At both ages, children were instructed to copy several 3D block constructions, followed by a “break” during which mothers and children were left alone with the blocks. A form that contained pictures of test items was left on the table. Video-recordings of mother-child interactions during the break were coded for two types of building behaviors – test-specific construction (building structures on the test form) or free-form construction (building structures not on the test form). Chinese children outperformed Mexican, African American, and Dominican children on the block-building assessment. Further, Chinese and Mexican mother-child dyads spent more time building test-specific constructions than did African American and Dominican dyads. At an individual level, mothers’ time spent building test-specific constructions at the 4-year (but not 5-year) assessment, but not mothers’ initiation of block building interactions or verbal instructions, related to children’s performance, when controlling for ethnicity. Ethnic differences in children's block-building performance and experiences emerge prior to formal schooling and provide a valuable window into sources of individual differences in early spatial cognition.